Efektivitas Penerimaan Dan Pelaporan Program Pengungkapan Sukarela Di Kantor Wilayah Direktorat Jenderal Pajak Sulawesi Selatan, Barat Dan Tenggara - Wisudawan, Akhmad Luthfi; Ilham, Ilham; Burhan, Imron (PT Bone Jaya Kreatif, 2023)
The research objective is to find out the effectiveness of receiving and reporting on the voluntary disclosure program in 2022 at the Regional Office of the Directorate General of Taxes in South, West, and Southeast Sulawesi. This type of research is a qualitative research is information data in the form of variable sentences not in the form of numeric symbols or numbers. The data used in this study are primary data and secondary data. The result of the research is the effectiveness of the Receipt and Reporting of the Voluntary Disclosure Program in 2022 at the Regional Offices of the Directorate General of Taxes in South, West, and Southeast Sulawesi, which can be seen based on indicators, namely receipts and reporting. These indicators show effective results. Voluntary Disclosure Program participants are not subject to sanctions in Article 18 paragraph (3) of the Tax Amnesty Law (200% of underpaid income tax) and data/information originating from SPPH cannot be used as a basis for investigation, investigation, and/or criminal prosecution against taxpayers